Gambaran Penggunaan Obat Antidepresan Pada Pasien Depresi Di RSUD Embung Fatimah Kota Batam Periode Januari - Desember 2020 - Rahmah Nurfahanum (Syntax Corporation Indonesia, 2022)
Background: Mental disorder is a condition in which a person experiences disturbances in thoughts, behavior, and feelings which are manifested in the form of a set of symptoms or significant behavioral changes, and can cause suffering and obstacles in carrying out people's functions as humans. The most common mental disorder is depression. More than 12 million people over the age of 15 are estimated to have experienced depression. This study aims to provide data on the use of antidepressants in depressed patients at Embung Fatimah Hospital, Batam City. Methods: This study was a descriptive observational study using secondary data from medical records. The research sample was all medical records of depressed patients who used antidepressants in depressed patients at Embung Fatimah Hospital, Batam City Period January - December 2020 that met the inclusion and exclusion criteria with the total sampling technique. Results: In this study, it was found that there were 44 out of 80 (55%) ) depressed patients at Embung Fatimah Hospital, Batam City who received antidepressant therapy. With the highest proportion at the age of 25-54 years (70.4%); female gender (56.8%). Amitriptyline (86.3%) and Sertralin (13.6%) were used. Conclusion: Most depressed patients at Embung Fatimah Hospital, Batam City received antidepressant therapy as a method of managing behavioral and psychological symptoms of depression